Sakinah Family Establishment in The Modern Era from The Perspectives of Hamka and Quraish Shihab - Amrullah, Mohammad Ghaffar; Ibrahim, Malik (Al-Mazaahib: Jurnal Perbandingan Hukum, 2021)
This article explains the concept of establishment of the sakinah family according to the perspective of Hamka and Quraish Shihab. This is a qualitative research which utilizes data sourced from literature. This article shows that according to Hamka, modern Sufism can be used as a solution to achieve a happy family in this world and the hereafter, regardless of the stigma that marriage is only to have children. Sufism does not only mean zuhud which is lonely, away from the world normally, but must actively work. As for the meaning of zuhud according to Hamka, is ready to be poor, rich, and to not have any penny, and on the other hand, being willing to become a millionaire, but wealth does not the cause of forgetting God, and neglecting the obligations. This is in line with the concept that taught by Islam, that Islam advocates the spirit to fight, the spirit of sacrifice and work not to be lazy. According to Quraish Shihab, The presence of sakinah does not just come, but there is a condition for its presence, the heart must be prepared with patience and piety.